Cucumber(Cucumis SativusL.)Growth and Nutrient ContentResponse to Applications of Leonarditeand Phosphorus Fertilizer - Ardalan Jalal Majeed (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2021)
Leonardite is a common mineral that contains a lot of organic matter. It may have a beneficial influence on plant growth and nutritional content. The objective of the present study was to determine the effect of four different leonardite doses (0, 20, 35, and 50 g kg-1), three different phosphor rates (0, 50, 100, and 150 mg kg-1P), on plant growth, and nutrient uptake of Cucumber (Cucumis sativusL.). plants. The experiment was conducted in a plastic house. Increasing the leonardite dose statistically increased the concentrations of N, P, K, Mg, Cu, and Mn in the cucumber leaves, but Zn content (34.711 a) mg kg-1of the leaves was significantly higher only with the (20 gm) of leonardite. The highest phosphor application (150 mg kg-1) increased leaf N, P, K, Ca, Mg, and Mn concentrations compared with the other three doses and also the leaf Zn levels statistically did not increase as the P applications increased from (control to 150 mg kg-1). Based on the number of fruits per plant, the best interaction among leonardite doses and phosphor rate were a combination of the (35gm×100 mg kg-1) increasing the numbers of cucumber per plant (48.000a).